Advances in the comprehensive mechanisms, diagnosis, and treatment of heatstroke-induced coagulopathy - Xiang, Chuhan; Gao, Ling; Liu, Xuhui; Xiang, Jun; Zhu, Bin; Fu, Shihui; Zhao, Jianhui; Song, Qing (Frontiers in Cell and Developmental Biology, 2025)
Heatstroke (HS) is a life-threatening condition that is precipitated by heat stress. The coagulation disorder that consequentially develops is termed heatstroke-induced coagulopathy (HIC). HIC typically presents as either hypocoagulopathy or hypercoagulopathy and is a principal complication that contributes to HS-associated mortality. There is no current consensus regarding HIC pathophysiology and specific pharmacological treatments. We review the diagnostic approaches, underlying mechanisms, and therapeutic interventions for HIC, with a particular emphasis on pharmacological treatments that include replacement therapy, anticoagulant therapy, traditional Chinese medicine, and novel therapies. The aim of this study is to enhance HIC awareness among clinicians and researchers and discuss the latest treatment strategy advancements to ultimately facilitate comprehensive HIC management and reduce its mortality rate.